Pendekatan Ekspositori dalam Penyutradaraan Video Feature “Meraih Upah di Balik Sampah” sebagai Representasi Kehidupan Pemulung di Kampung Pemulung Jurangmangu Barat - Puji Marsyanda Ika Rahayu; Kania Az Zahra; Pandu Watu Alam (Jurnal Nusantara Berbakti, 2026)
The feature video titled “Earning Wages Behind Waste” portrays the lives of a waste picker community in Kampung Pemulung, Jurangmangu Barat, South Tangerang, as a concrete representation of the social dynamics of urban society. This study aims to represent the social reality of waste pickers as part of urban community dynamics through an informative and systematic expository directing approach. The creative process was carried out through three main stages pre-production, production, and post-production which were integrated to produce a coherent, structured, and easily understandable narrative flow for the audience. The expository approach is applied through the use of narration as the primary guiding element to explain the visual context, supported by a logical presentation structure, interviews with informants, and relevant factual data. In the directing process, the author actively organizes the flow of information and integrates visual elements, narration, and interviews to produce a work that is informative, contextual, and educational. Furthermore, cinematographic aspects such as shot variation and camera movement are utilized to support the gradual delivery of information, reinforce visual messages, and maintain objectivity in presentation. The results indicate that the expository approach is effective in presenting the factual reality of waste pickers’ lives and in enhancing audience understanding of their socio-economic conditions in a more comprehensive manner.